Factors affecting "entrepreneurial culture": The mediating role of creativity - Rizwan Qaisar Danish; Javeria Asghar; Zeeshan Ahmad; Hafiz Fawad Ali (Journal of Innovation and Entrepreneurship, 2019)
Entrepreneurial culture has been an area of worth investigation in management research for many years since the growth in technology-based business ventures. In the context of businesses, entrepreneurial culture may be described as attitudes, values, skills, and power of a group or individual working in an organization that is characterized by risk. The prime purpose of this study is to examine the effect of openness to change and self-efficacy on entrepreneurial culture with the mediating role of creativity. We have used innovative culture as a substitute to measure the entrepreneurial culture of an organization due to its prognosticator power. Self-administered questionnaires were distributed through physical channel among employees of various firms engaged in the information technology business. Specifically, we collected data from all registered firms in the capital city of the Province Punjab, thus making an overall sample size of 300 and useable questionnaires that were returned filled for analysis were 225 (useable response rate 75%) employees of various private firms. For the analysis purpose and to explain the relationships among variables and mediational effects, we have used SPSS and AMOS for SEM. The findings clearly report that there are significant direct relationships among variables such that openness to change and self-efficacy have a positive impact on entrepreneurial culture, as well as in the presence of creativity as a mediator. The limitations of this study have been discussed with its theoretical and practical contribution. Future researchers can focus on longitudinal study and use qualitative methods for in-depth knowledge along with other variables in order to measure entrepreneurial culture in a broader way.
Keywords: 650; Entrepreneurial culture; Openness to change; Self-efficacy; Creativity; Innovation